Analisis Audit Energi Listrik di Balai Pelatihan Vokasi dan Produktivitas Bantaeng - Gunawan Thamrin, Hendra; Hamzah, Nur; Yusuf Yunus, Muhammad (Jurnal Teknik Mesin Sinergi, 2025)
An electrical energy audit is a systematic process of evaluating energy consumption in a building or facility in order to identify energy efficiency and potential savings. energy use and potential savings. This research aims to conduct an electrical energy audit in order to determine the intensity of energy consumption (IKE) and provide technical recommendations that support energy efficiency in the office of the Bantaeng Vocational and Productivity Training Center. The energy audit was conducted by collecting electricity consumption data from PLN billing records as well as direct measurements in the field. The analysis focused on the calculation of Energy Consumption Intensity (ECI) to assess the energy performance of the building. The audit results show that the intensity of energy consumption (IKE) for one year, the value of energy consumption intensity (IKE) for one year, the value is 12.8 kWh/m2/year which means it is still below the ASEAN-USAID standard of 240 kWh/m2/year. Likewise, compared to the IKE standard according to the Regulation of the Minister of Energy and Mineral Resources No. IX. Minister of Energy and Mineral Resources Regulation No. 3 of 2025 which is <99 kWh/m2/year with a total building area of 11,644 m2 > 5000 m2 is categorized as very efficient.